Patofiziologija skeletne mišice pri cerebralni paralizi - Matkovič, Urška (Fizioterapija (Ljubljana), 2016)
Cerebral palsy is a clinical syndrome characterized primarily, but not exclusively, by movement and posture disorders, which arise due to injury to the developing brain. This injury directly and indirectly leads to contractures, which limit range of joint motion. Contractures develop due to functional and structural alterations affecting the stretch reflex and skeletal muscle. In the early stages of spastic cerebral palsy joint motion is limited mainly due to increased muscle tone, which is caused by overactivity of the stretch reflex. Later on, structural alterations in skeletal muscle lead to fixed contractures, which are characterized by shorter muscle fibers and hypertrophy of the extracellular matrix. Mechanisms by which injury to the developing brain leads to structural alterations in skeletal muscle are obscure. Interestingly, recent findings suggest that the number of muscle satellite cells is reduced in cerebral palsy, which may directly contribute to development of contractures. This mechanism, if confirmed, might lead to novel therapeutic approaches for contractures in cerebral palsy.
Keywords: cerebral palsy; cerebralna paraliza; skeletal muscle; skeletne mišice; spasticity; spastičnost